FDI on Tourism and the Environmental Damage: What Indonesia’s Trade and Investment Agreements Can Do? - I Gusti Ngurah Parikesit Widiatedja (Universitas Airlangga, 2019)
The existence of FDI on tourism has provided benefits, covering job opportunities, transfer of technology, government revenue, and the partnership with small and medium enterprises. However, FDI on tourism has also contributed to environmental damage in Indonesia. This paper is aimed to analyse whether trade and investment agreements that involve Indonesia can contribute to prevent and mitigate environmental damage as a result from FDI on tourism. This article is normative research, examining the existing trade and investment agreements that involve Indonesia and compare them with other countries’ agreements. This paper argues that there is evidence to suggest that trade and investment agreements may incorporate provisions in order to ameliorate environmental harm from the existence of FDI on tourism. However, Indonesia has not incorporated any such provisions in its own agreements. Hence, this paper explains that there will be three suggestions to be considered, namely: Indonesia should start putting environmental concern under its trade schedule; Indonesia should consider opening environmental services; and Indonesia should start putting environmental concern in its investment agreements.